Peningkatan Layanan Dan Pengelolaan Risiko Dalam Industri Haji Dan Umroh - Ramadhan Ayyasy; Akyas Izhdhihari Ahmad; M. Ibnu Maulana (Maslahah : Jurnal Manajemen dan Ekonomi Syariah, 2024)
The Hajj and Umrah industry is an important sector involving millions of pilgrims every year. The complexity of organizing this worship service requires improved services and effective risk management to ensure the smooth running and comfort of the congregation. This research aims to explore strategies for improving services and risk management in the Hajj and Umrah industry. The research method used is qualitative with literature studies from various trusted sources. The research results show that service quality is greatly influenced by staff friendliness, service reliability, facility cleanliness, and timeliness. In addition, identifying and mitigating health, security and logistics risks is critical to reducing negative impacts on congregations. Technological innovations, such as mobile applications, have also been proven to improve efficiency and service quality. This research provides recommendations for the government and Hajj and Umrah organizers to improve service quality and risk management, so that pilgrims can carry out their worship more safely and comfortably.